Novel characterization technique by using an SEM - Sutjipto, Agus Geter Edy; -, Jufriadi; Muhida, Riza; Takata, Masasuke (2008)
Charging and discharging phenomenon on the surface of materials can be found in plasma display panel, spacecraft charging, high voltage insulator, etc. This report gives a simple explanation on this phenomenon. A scanning electron microscope was used not only as a tool to produce energetic electron beam to charge an insulator without metallic coating and to produce a surface discharging (surface breakdown/flashover) but also to observe the visible charging and discharging on the sample surface. A model of electric field distribution on the surface was developed in order to explain charging and discharging phenomena. Since charging and discharging process involves incubation time, therefore this process can be used to characterize or evaluate the insulation property of materials under electron bombardment.